Auditory Training for Everyday Functioning in Later Life - Li, Karen Z. H.; Campos, Jennifer; Pichora-Fuller, Margaret K. (Seminars in Hearing, 2025)
Following from the World Health Organization's consideration of multiple systems (e.g., sensory, motor, and cognitive) in defining healthy aging, this study presents a review of research on training that has the primary goal of improving complex multitasking outcomes that approximate the everyday contexts in which hearing is important, whether or not older adults are living with clinically significant audiometric hearing loss. Background on the interplay between sensory, motor, and cognitive systems establishes the rationale for considering complex listening behaviors as primary outcomes, and for focusing training on domain-free executive function (EF) processes such as selection, inhibition, and working memory updating. Approaches to cognitive training in later life are discussed to provide a foundation for a deeper examination of targeted EF training and complex listening outcomes that reflect performance in everyday activities. Where available, studies involving older adults with hearing loss are included, although many studies include a mixture of older adults with good audiograms, sub-clinical audiometric loss, or clinically significant but untreated audiometric loss. Overall, the reviewed literature suggests that older adults, with or without audiometric hearing loss, can benefit from EF training that improves complex listening performance. Future clinical considerations are discussed, including rehabilitation that extends from communication training to realistic multitasking training.
Keywords: multitasking; training; executive functions; everyday activity; hearing loss